Outcome of Surfactant-Administration in Neonates with “Meconium-Aspiration-Syndrome” - Samina Shams Alam, Muhammad Ishaq, Kaneez Fatima (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Combined Military Hospital in Rawalpindi, surfactant treatment to newborns with meconium aspiration syndrome (MAS) was studied for its effectiveness. 100 newborns with MAS who underwent surfactant treatment between [30 June] 2021 and [30 July] 2022 were a part of this prospective trial. Mortality, the need for oxygen, the demand for mechanical ventilation, and the duration of hospital stay were the main outcome measures. The frequency of pneumothoraxes used as the secondary outcome indicator. The study’s findings demonstrated that the administration of surfactants considerably decreased mortality [03%] vs [10%] oxygen consumption [50%] vs. [71%], the need for mechanical breathing [20%] vs. [45%], and hospital stay [05-06] days vs. [08-05] days. Additionally, there was a considerable reduction in the incidence of pneumothorax [10%] vs. [15%]. These results imply that the use of surfactants might lessen the mortality and morbidity linked to MAS in newborns. Aim: Combined Military Hospital Rawalpindi’s newborns with meconium aspiration syndrome (MAS) were the subject of this research to determine the effects of surfactant treatment. It evaluated both the treatment’s main and secondary results. Methods: The Department of Neonatology at the Combined Military Hospital in Rawalpindi performed this prospective research on a sample of hundred newborns with MAS who underwent surfactant treatment between [June 30], 2021, and [July 30] 2022. Mortality, the need for oxygen, the demand for mechanical ventilation, and the duration of hospital stay were the main outcome measures. The frequency of pneumothoraxes used as the secondary outcome indicator. Results: The study’s findings demonstrated that the administration of surfactants considerably decreased mortality [03%] vs [10%], oxygen consumption [50%] vs [71%], the need for mechanical breathing [20%] vs [45%] and hospital stay [5-6 days] vs [8-5 days]. Additionally, there was a considerable reduction in the incidence of pneumothorax (10% vs. 15%). Conclusion: the use of surfactants might lessen the mortality and morbidity linked to MAS in newborns. Keywords: Surfactant, Neonates, Results, Meconium Aspiration Syndrome